Genotyping of long term persistent Staphylococcus aureus in bovine subclinical mastitis - Rossi, B. F. [UNESP]; Bonsaglia, E. C. R. [UNESP]; Castilho, I. G. [UNESP]; Dantas, S. T. A. [UNESP]; Salina, A. [UNESP]; Langoni, H. [UNESP]; Pantoja, J. C. F. [UNESP]; Budri, P. E.; Fitzgerald-Hughes, D.; Fernandes Junior, A. [UNESP]; Rall, V. L. M. [UNESP] (Elsevier B.V., 2019)
Bovine mastitis affects dairy cattle worldwide and Staphylococcus aureus is one of the most common microorganisms involved in subclinical and chronic disease. Superantigens, such as enterotoxins contribute to S. aureus persistence and pathogenicity in this disease. Subclinical and chronic mastitis cases were diagnosed and S. aureus isolates from sub-clinical cases were investigated for carriage of virulence and antibiotic resistance genes that may contribute to long-term carriage and infection. Over a 12-month period, 116 S. aureus strains were recovered from 68 cows with subclinical mastitis. Classical enterotoxin genes (sea-see) were detected in 24.1% of isolates, and pvl and tsst-1 were identified in 3.4% and 46.6% the isolates, respectively. 18.1% that were persistent isolates were identified and characterized by pulsed field gel electrophoresis (PFGE), MLST, spa typing. Four isolates were methicillin-resistant S. aureus (MRSA) and belonged to SCCmec type I. Molecular typing showed that the agrI group was the most frequent, and a rare isolate was positive for both agrI and agrIII groups. Molecular characterization revealed the persistence of the spa type t10856 (ST133, clonal complex CC133, agr I), in a single animal for nine months and the persistence t605 (ST126, CC126) colonizing four animals for four months. These strains have been described recently in other herds in the same region, indicating their transmissibility and clonal expansion. We conclude that animals with subclinical mastitis are an important and somewhat overlooked reservoir for transmission within and between herds, and may carry virulence and antibiotic resistance genes contributing to persistent colonization, hinder the control of mastitis and may cause risks to the public health.
Keywords: agr; PFGE; spa-type; Persistence